The loan puzzle in Mexico - Luis Fernando Colunga (Banco de México, 2024)
In some advanced and emerging economies, contrary to expectations, it has been observed that increases in short-term interest rates are accompanied by increases in bank credit; a phenomenon referred to as "the loan puzzle." This study investigates, through the estimation of a structural vector autoregressive model using national and sectoral-level data, whether this phenomenon occurred in the Mexican economy between 2001 and 2019. The results suggest that, in response to a positive shock to short-term interest rates, the volume of bank credit to firms exhibits a positive and short-lived response but subsequently decreases. This response is primarily observed in sectors that had the lowest average delinquency rates during the analysis period. This suggests that banks would grant more loans to relatively safer companies, while, in response to such monetary tightening, they would reduce their investments in riskier and longer-term assets, such as consumer loans and loans to the real estate sector.
Keywords: E51; E52; E58; 330; Monetary Policy; Bank Credit; Vector Autoregressive Model